2018
DOI: 10.2139/ssrn.3139024
|View full text |Cite
|
Sign up to set email alerts
|

Does Exchange Rate Depreciation Have Contractionary Effects on Firm-Level Investment?

Abstract: WP624 Does exchange rate depreciation have contractionary effects on firm-level investment? 1 Does exchange rate depreciation have contractionary effects on firm-level investment? The implications of alternative types of bond financing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
2
16
0
1
Order By: Relevance
“…Section 5 concludes and provides some policy implications. 9 While we use a new firm-level dataset with comprehensive information on Asian firms' FX liabilities, our results are consistent with those of Alfaro et al (2017) and Serena and Sousa (2017). Alfaro et al (2017) find that the interaction between the firms' overall leverage and depreciation of domestic currency against USD negatively impact the firms' Z''-score.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Section 5 concludes and provides some policy implications. 9 While we use a new firm-level dataset with comprehensive information on Asian firms' FX liabilities, our results are consistent with those of Alfaro et al (2017) and Serena and Sousa (2017). Alfaro et al (2017) find that the interaction between the firms' overall leverage and depreciation of domestic currency against USD negatively impact the firms' Z''-score.…”
supporting
confidence: 70%
“…We show that FX loans indeed explain the results. Serena and Sousa (2017) find that the interaction between domestic currency depreciation and the amount of USD denominated bond on firms' balance sheet is negatively correlated with firms' investment. Our paper goes beyond the existing literature by providing a comprehensive measure of leverage in USD, including both bank loan and bond issuances.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…For firm‐level variables, we follow Serena and Sousa () and use the dividend ratio (DPR), to control for the degree of financial constraints. Recent literature has shown that financial constraints matter for the firms’ risk and expected returns (see Lamont, Polk, & Saaá‐Requejo, ; Livdan, Sapriza, & Zhang, ; Whited & Wu, ).…”
Section: Empirical Strategymentioning
confidence: 99%
“…13 Furthermore, for emerging and developing economies, even small currency depreciations are often contractionary events. If domestic firms and banks borrow in dollar, but equity is denominated in domestic currency, a depreciation, increases debt service payments and lowers the capacity to invest (see Serena and Sousa, 2017). Moreover, investment may decline further due to an international borrowing constraint: after a depreciation the collateral value of assets denominated in domestic currency falls and makes it more difficult to borrow from abroad (see Braggion, Christiano, and Roldos, 2009).…”
Section: B State-dependent Effectsmentioning
confidence: 99%